Phase change microcapsule composite aerogel thermal insulation material and preparation method thereof
By using a gradient composite design of phase change microcapsule composite aerogel insulation material, the problems of high thermal conductivity and short service life of traditional phase change panels are solved, achieving dynamic heat regulation and long-term insulation performance, thus improving the overall performance and service life of building insulation materials.
Patent Information
- Application Number
- CN202511066446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional phase change plates have high thermal conductivity, which cannot effectively suppress heat conduction during the heat transfer process, resulting in energy loss. Furthermore, the insulation performance decreases significantly during the phase change process, making it difficult to maintain a stable indoor temperature and limiting the service life.
The phase change microcapsule composite aerogel insulation material is adopted. Through the composite design of phase change energy storage layer and thermal insulation layer, materials such as glass microspheres, hydrophobic aerogel powder, cenospheres, expanded perlite and carbon black are used. Combined with segmented roller process and adhesive, a gradient composite structure is formed to achieve dynamic heat regulation and long-term heat preservation performance.
It effectively reduces heat conduction, maintains stable indoor temperature, improves the material's overall thermal management performance in a wide temperature range, extends service life, and reduces production costs.
Smart Images

Figure CN120987624A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a kind of phase change microcapsule composite aerogel thermal insulation material and its preparation method, belong to building thermal insulation material technical field. BACKGROUND
[0002] With the increasing of building energy-saving standards, the performance of building thermal insulation materials is increasingly concerned. Among many thermal insulation materials, phase change board has been widely used in building thermal insulation field due to its characteristics of phase change and absorbing or releasing a large amount of latent heat in a specific temperature range. It can effectively regulate indoor temperature fluctuations and reduce the energy consumption of air conditioning, heating and other equipment.
[0003] However, traditional phase change boards have many insurmountable shortcomings. From the material intrinsic characteristics, traditional phase change materials such as paraffin or fatty acid have high thermal conductivity, usually ≥0.2 W / (m·K), which means that in the process of heat transfer, heat will quickly pass through the phase change board, resulting in a large amount of energy loss. When the outdoor temperature changes, the indoor temperature will also fluctuate quickly, making it difficult to maintain a stable indoor thermal environment. During the phase change process, although the phase change board can absorb or release heat, its thermal insulation performance will decrease sharply once the phase change is completed. For example, at night, when the outdoor temperature continues to decrease, the phase change board after phase change cannot effectively block the heat loss, and the indoor temperature will gradually decrease, which not only affects the comfort of living, but also increases the operation time and energy consumption of heating equipment.
[0004] In addition, the service life of traditional phase change boards is limited. Due to long-term exposure to temperature changes, its internal structure is easily damaged by thermal stress, resulting in gradual degradation of phase change performance and thermal insulation performance. Moreover, the existing phase change boards often have complex production processes and high costs, which also limit their large-scale application. These problems urgently need to be solved by innovative materials and preparation methods to meet the demand for efficient, energy-saving and long-life thermal insulation materials in modern buildings. SUMMARY
[0005] (I) Technical problems to be solved
[0006] To solve the problem of high thermal conductivity of traditional phase change boards in the prior art, which cannot effectively inhibit heat conduction in the process of heat transfer, resulting in a large amount of energy loss and inability to maintain stable indoor temperature, especially during the phase change process, lack of effective thermal insulation mechanism, difficult to continuously play the role of thermal insulation, leading to rapid heat loss in the room, the present application provides a kind of phase change microcapsule composite aerogel thermal insulation material and its preparation method.
[0007] (II) Technical solutions
[0008] To achieve the above purpose, the main technical solutions adopted by the present application include:
[0009] A phase change microcapsule composite aerogel thermal insulation material, comprising a phase change energy storage layer and a thermal insulation layer, wherein the phase change energy storage layer is prepared from energy storage powder and a binder, the energy storage powder comprising thermal insulation material, phase change material, flame retardant and fiber; the thermal insulation layer is prepared from thermal insulation powder and a binder, the thermal insulation powder comprising thermal insulation material, flame retardant and fiber.
[0010] In the energy storage powder and the thermal insulation powder, the thermal insulation material is a combination of glass microspheres, hydrophobic aerogel powder, floating beads, expanded perlite and carbon black; the phase change material is phase change microcapsule; the flame retardant is a combination of montmorillonite, talc powder and magnesium hydroxide; the fiber is a combination of glass fiber, nylon fiber and cellulose fiber; the binder comprises polyvinyl alcohol, boric acid and silica sol; during preparation of the phase change energy storage layer and the thermal insulation layer, the binder is configured into a bonding liquid together with water, defoaming agent and hydrophobic agent.
[0011] The phase change microcapsule composite aerogel thermal insulation material as described above, preferably, the thermal insulation material is 56-90 parts by mass, the phase change material is 30-40 parts by mass, the flame retardant is 12-23 parts by mass, the fiber is 3-6 parts by mass; the binder is 33-52 parts by mass, the defoaming agent is 1-2 parts by mass, the water is 250-350 parts by mass, and the hydrophobic agent is 20-30 parts by mass; the defoaming agent is tributyl phosphate, the hydrophobic agent is calcium stearate emulsion, the polyvinyl alcohol is polyvinyl alcohol 1788 and polyvinyl alcohol 2488.
[0012] The phase change microcapsule composite aerogel thermal insulation material as described above, preferably, the thermal insulation material comprises 20-35 parts by mass of glass microspheres, 3-20 parts by mass of hydrophobic aerogel powder, 12-20 parts by mass of floating beads, 8-18 parts by mass of expanded perlite and 0.5-5 parts by mass of carbon black; the flame retardant comprises 3-10 parts by mass of montmorillonite, 2-9 parts by mass of talc powder and 1-5 parts by mass of magnesium hydroxide; the fiber comprises 0.5-3 parts by mass of glass fiber, 0.5-2.5 parts by mass of nylon fiber and 0.5-2.5 parts by mass of cellulose fiber.
[0013] The phase change microcapsule composite aerogel thermal insulation material as described above, preferably, the thermal insulation material comprises 25-30 parts by mass of glass microspheres, 5-15 parts by mass of hydrophobic aerogel powder, 15-18 parts by mass of floating beads, 10-15 parts by mass of expanded perlite and 2-1 parts by mass of carbon black; the flame retardant comprises 5-8 parts by mass of montmorillonite, 5-7 parts by mass of talc powder and 2-3 parts by mass of magnesium hydroxide; the fiber comprises 1-2 parts by mass of glass fiber, 1-2 parts by mass of nylon fiber and 1-2 parts by mass of cellulose fiber.
[0014] The preparation method of the phase change microcapsule composite aerogel thermal insulation material as described above, comprising the following steps:
[0015] S1, polyvinyl alcohol 1788 and polyvinyl alcohol 2488 are mixed and stirred to dissolve in water, and then a solution A is obtained;
[0016] S2, boric acid is dissolved in water, then silica sol is added, stirred uniformly, the pH value is adjusted to weak alkaline, hydrophobic agent is added and stirred uniformly, and then a solution B is obtained;
[0017] S3, solution A and solution B are mixed, defoaming agent is added and defoamed to obtain a bonding liquid;
[0018] S4, the thermal insulation material, the phase change material, the flame retardant and the fiber are mixed uniformly, and then mixed with the bonding liquid to obtain a phase change energy storage layer plastic state mixture;
[0019] S5, the thermal insulation material, the flame retardant and the fiber are mixed uniformly, and then mixed with the bonding liquid to obtain a thermal insulation layer plastic state mixture;
[0020] S6, the phase change energy storage layer plastic state mixture and the thermal insulation layer plastic state mixture are uniformly compounded and formed into a slab under the action of segmented extrusion by using a segmented roller process;
[0021] S7, the formed slab is first solidified, and then dried to obtain a thermal insulation material.
[0022] The preparation method described above, preferably in step S1, the stirring and dissolving is carried out at 80-100℃, the stirring rate is 2000-3000r / min, and the stirring time is 1.5-3h.
[0023] The preparation method described above, preferably in step S2, the pH value is adjusted to 7.5 by using an acidic reagent; the stirring rate for uniform mixing is 1500-2500r / min, and the stirring time is 2-4min.
[0024] The preparation method described above, preferably in steps S4 and S5, the stirring rate for mixing with the bonding liquid is 200-300r / min, and the stirring time is 2-5min.
[0025] In a preferred embodiment, in step S6, the pressure of segmented extrusion in the segmented roller process is 0.3-0.5MPa, and the roller rotation speed is 25-30mm / s.
[0026] In step S6, a segmented roller press process is used to prepare the insulation material. The roller press system applies the same pressure and speed at different stages to achieve gradient composite and structural control of the multilayer material. A three-stage process is adopted: first, the phase change energy storage layer or the thermal insulation layer is extruded; then, the remaining layer is extruded; and finally, the two layers are extruded together. Through segmented control, the phase change energy storage layer and the thermal insulation layer gradually fuse during the extrusion process, forming a composite structure with uniform interface transition and gradient performance changes. The pre-compression stage initially compacts the mixture of the two layers separately to remove air bubbles; the composite stage uses pressure to allow the interfaces of the two materials to permeate each other, ensuring structural stability. Compared to the traditional single-roller process, the segmented process can more precisely control the interlayer bonding strength and functional gradient, avoiding rupture and leakage of the phase change microcapsule material due to excessive extrusion.
[0027] In a preferred embodiment, in step S7, the curing temperature is 60-80°C and the curing time is 6-7 hours; the drying temperature is 100-130°C and the drying time is 12-13 hours.
[0028] (III) Beneficial Effects
[0029] The beneficial effects of this invention are:
[0030] This invention provides a phase change microcapsule composite aerogel insulation material. Through the combination of a phase change energy storage layer and a thermal insulation layer, the low thermal conductivity aerogel layer (i.e., the thermal insulation layer) insulates heat on the heated surface. As heat is gradually transferred, the phase change microcapsule aerogel layer (i.e., the phase change energy storage layer) responds to changes in ambient temperature on the cooled surface, achieving dynamic heat regulation. Simultaneously, the microcapsules and aerogel within the material work synergistically, continuously exhibiting excellent thermal insulation performance during and after the phase change process, effectively reducing heat conduction. This composite structure of phase change energy storage and thermal insulation layer overcomes the technical bottlenecks of traditional phase change plates, such as low heat regulation efficiency during the phase change process and poor thermal insulation effect after the phase change. Through the composite design of phase change energy storage and thermal insulation, the overall thermal management performance of the material is significantly improved in a wide temperature range environment.
[0031] This invention provides a method for preparing a phase change microcapsule composite aerogel insulation material. It employs a roller-rolling process to composite a phase change energy storage layer material with an aerogel insulation substrate of a thermal insulation layer. By controlling the distribution density of phase change microcapsules in the composite board and optimizing the ratio parameters of phase change material and insulation material in the phase change layer, it achieves good thermal insulation function while the phase change material absorbs / releases heat, effectively solving the problem of poor thermal insulation performance of traditional phase change boards. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the structure of a gradient composite phase change microcapsule aerogel plate;
[0033] Figure 2A preparation method flowchart of the phase change microcapsule composite aerogel thermal insulation material provided by the application is shown in the figure.
[0034] Figure 3 A schematic diagram of the uniform phase change structure is shown in the figure.
[0035] Figure 4 A schematic diagram of the uniform thermal insulation board structure is shown in the figure.
[0036] Figure 5 Test results of the heating table test.
[0037] [Explanation of reference signs]
[0038] 1: phase change energy storage layer
[0039] 2: thermal insulation layer
[0040] 3: hot surface
[0041] 4: uniform phase change board
[0042] 5: uniform thermal insulation board DETAILED DESCRIPTION
[0043] The application provides a phase change microcapsule composite aerogel thermal insulation material and a preparation method thereof, and aims to solve the problem that the thermal insulation performance of traditional phase change materials significantly decreases after phase change is completed. The preparation of the phase change microcapsule composite aerogel thermal insulation material provided by the application innovatively realizes the synergistic optimization of the phase change heat storage function and the thermal insulation function of the material by precisely regulating the concentration distribution of the phase change microcapsule in the aerogel matrix, and meanwhile, the directional regulation of the synergistic effect of the two is realized by optimizing the matching parameters of the phase change material and the thermal insulation material.
[0044] The phase change microcapsule composite aerogel thermal insulation material provided by the application comprises a phase change energy storage layer and a thermal insulation layer, wherein the phase change energy storage layer is prepared from energy storage powder and an adhesive, the phase change energy storage powder comprises a thermal insulation material, a phase change material, a flame retardant and a fiber; the thermal insulation layer is prepared from thermal insulation powder and an adhesive, the thermal insulation powder comprises a thermal insulation material, a flame retardant and a fiber; the thermal insulation material is glass microspheres, hydrophobic aerogel powder, floating beads, expanded perlite and carbon black; the phase change material is phase change microcapsules; the flame retardant is montmorillonite, talcum powder and magnesium hydroxide; the fiber is glass fiber, nylon fiber and cellulose fiber; the adhesive comprises polyvinyl alcohol, boric acid and silica sol, and deionized water, a defoaming agent and a hydrophobic agent are added to the adhesive to configure a bonding liquid for use. The structure schematic diagram of the phase change microcapsule composite aerogel thermal insulation material is shown in Figure 1, the phase change energy storage layer 1 is arranged above the thermal insulation layer 2, and the hot surface 3 is the surface in contact with the thermal insulation layer 2.
[0045] Further, the thermal insulation material is 56-90 parts by mass, the phase change material is 30-40 parts by mass, the flame retardant is 12-23 parts by mass, and the fiber is 3-6 parts by mass; the adhesive is 33-52 parts by mass, the defoaming agent is 1-2 parts by mass, the deionized water is 250-350 parts by mass, and the hydrophobic agent is 20-30 parts by mass; the defoaming agent is tributyl phosphate, the hydrophobic agent is calcium stearate emulsion, and the polyvinyl alcohol is polyvinyl alcohol 1788 and polyvinyl alcohol 2488.
[0046] Further, the thermal insulation material comprises glass microspheres 20-35 parts, hydrophobic aerogel powder 3-20 parts, floating beads 12-20 parts, expanded perlite 8-18 parts, and carbon black 0.5-5 parts; the flame retardant comprises montmorillonite 3-10 parts, talc powder 2-9 parts, and magnesium hydroxide 1-5 parts; and the fiber comprises glass fiber 0.5-3 parts, nylon fiber 0.5-2.5 parts, and cellulose fiber 0.5-2.5 parts.
[0047] Further preferably, the thermal insulation material comprises glass microspheres 25-30 parts, hydrophobic aerogel powder 5-15 parts, floating beads 15-18 parts, expanded perlite 10-15 parts, and carbon black 2-1 parts; the flame retardant comprises montmorillonite 5-8 parts, talc powder 5-7 parts, and magnesium hydroxide 2-3 parts; and the fiber comprises glass fiber 1-2 parts, nylon fiber 1-2 parts, and cellulose fiber 1-2 parts.
[0048] The application also provides a preparation method of the phase change microcapsule composite aerogel thermal insulation material, a flowchart of which is shown in Figure 2 as shown, and specifically comprises the following steps:
[0049] S1, polyvinyl alcohol is mixed with water and stirred to dissolve, serving as solution A;
[0050] S2, boric acid is dissolved in water, then silica sol is added, stirred to be uniform, and then the pH value is adjusted, then a hydrophobic agent is added and stirred to be uniform, serving as solution B;
[0051] S3, solution A and solution B are mixed, a defoaming agent is added to defoam, and then a bonding liquid is obtained;
[0052] S4, the thermal insulation material, the phase change material, the flame retardant, and the fiber are mixed, and then mixed with the bonding liquid to obtain a phase change energy storage layer plastic state mixture;
[0053] S5, the thermal insulation material, the flame retardant, and the fiber are mixed, and then mixed with the bonding liquid to obtain a thermal insulation layer plastic state mixture;
[0054] S6, the phase change energy storage layer plastic state mixture and the thermal insulation layer plastic state mixture are uniformly compounded and formed by a segmented roller process under the action of segmented extrusion to obtain a plate;
[0055] S7, solidify the formed plate first, and then dry to obtain a phase change microcapsule composite aerogel plate.
[0056] The present application is obtained through a large number of experimental researches. In the thermal insulation material used in the present application, glass microspheres are preferably used as the main thermal insulation framework. The glass microspheres have a hollow structure (thin wall, air inside), a very low thermal conductivity, and can effectively block heat conduction. The glass microspheres have a small density, can reduce the overall weight of the plate, and at the same time provide a dispersion space for the phase change material, so as to avoid structural damage caused by volume expansion during phase change. The content of the glass microspheres is preferably in the range of 20-35 parts, which can ensure good heat insulation performance while maintaining the appropriate density and strength of the plate. The glass microspheres have the characteristics of light weight, high strength and low thermal conductivity, and can effectively block heat transfer. The content of the glass microspheres is most preferably 25-30 parts. The hydrophobic aerogel powder used has a super-insulation synergistic effect. The hydrophobic aerogel powder has a nano-porous structure (porosity > 90%) that can inhibit air convection and thermal radiation. The hydrophobic aerogel powder is also hydrophobic and moisture-proof after hydrophobic modification (such as silane treatment), which can avoid water absorption and solve the problem of heat insulation failure of traditional thermal insulation materials (such as expanded perlite) after absorbing moisture. The drying step of S7 cooperates to ensure long-term heat insulation. The content of the hydrophobic aerogel powder is preferably 3-20 parts, which can greatly improve the heat insulation performance of the material without affecting the overall molding process. The hydrophobic aerogel powder is a high-efficiency thermal insulation material, and its very low thermal conductivity can significantly reduce the heat conduction rate. The content of the hydrophobic aerogel powder is most preferably 5-15 parts. The float beads have a high-temperature-resistant auxiliary thermal insulation effect and form a "hollow particle grading" with the glass microspheres to fill the gaps between each other and reduce the thermal bridge effect. The float beads also have a cost balance: the price is lower than that of aerogel and glass microspheres, and a high dosage can control the cost while ensuring heat insulation. The content of the float beads is preferably 12-20 parts, which helps to control the cost while ensuring the performance. The float beads have good heat insulation performance and relatively low cost, and the content of the float beads is most preferably 15-18 parts. The expanded perlite has a porous heat storage adaptation and density adjustment effect. The expanded perlite has a porous structure and can absorb part of the phase change material to reduce liquid migration during phase change. The density of the expanded perlite is moderate (0.08-0.2 g / cm3), which can be combined with other lightweight materials to avoid insufficient mechanical strength caused by excessive lightness of the plate. The expanded perlite can also effectively hinder heat transfer, and the content of the expanded perlite is preferably 8-18 parts, which can further enhance the heat insulation effect. The carbon black has infrared light shielding, coloring and anti-aging effects. Aerogel, glass microspheres and other materials have weak infrared thermal radiation shielding ability (infrared radiation accounts for 40-50% of heat transfer), and the carbon black can absorb infrared light to reduce radiation heat transfer. The carbon black can also improve the electrical conductivity and thermal stability of the material to a certain extent. A small amount of carbon black can also shield ultraviolet rays, delay the aging of the adhesive (PVA) and fibers, and prolong the service life of the plate. The content of the carbon black is preferably 0.5-5 parts, which can play its role without negatively affecting other properties.
[0057] The adhesive is preferably polyvinyl alcohol, boric acid and silica sol, wherein the polyvinyl alcohol has good adhesion and water solubility, can be dissolved in water to form a viscous solution, and most preferably the polyvinyl alcohol is polyvinyl alcohol 1788 and polyvinyl alcohol 2488. The addition of boric acid and silica sol can further cross-link with polyvinyl alcohol to enhance the bonding strength; the addition of PVA and boric acid ensures the flexibility and adhesion of the adhesive, and the addition of silica sol improves the water resistance and structural stability of the system. The synergistic reaction of the three materials solves the problem of poor water resistance of PVA adhesive, and makes up for the defects of high brittleness and insufficient adhesion of silica sol, so that the final plate has high strength and high stability. The boric acid and silica sol in the adhesive are inorganic components, which have flame retardance and high temperature stability, and improve the flame retardance grade and temperature deformation resistance of the material.
[0058] The flame retardant used in the present application is preferably montmorillonite, talc powder and magnesium hydroxide, wherein the montmorillonite also has the functions of expanding into carbon insulation and inhibiting molten droplets. The montmorillonite can form a barrier layer during combustion to prevent the transfer of heat and oxygen, physically blocking the transfer of heat and oxygen to the inside, and can enhance the carbonization of the material, reduce the molten droplets during combustion, and especially inhibit the droplets of organic components such as nylon fibers. The preferred addition amount of montmorillonite is 3-10 parts, which can effectively improve the flame retardance of the material, and the most preferred is 5-8 parts. Talc powder has the effect of enhancing thermal stability and also has a synergistic effect on flame retardance. It can improve the thermal deformation temperature of the material and delay the structural damage of the hydrophobic aerogel powder at high temperature; it also acts as an inert filler, which can dilute the concentration of combustible components such as phase change materials and cellulose fibers, while promoting the uniform dispersion of montmorillonite and improving the continuity of the expanded carbon layer. It improves the processability of the material, and also has a certain flame retardant effect. The preferred addition amount of talc powder is 2-9 parts, which can ensure the flame retardant effect while making the material more easily shaped during preparation, and the most preferred is 5-7 parts. Magnesium hydroxide can absorb a large amount of heat when heated, which plays a role in reducing temperature and flame retardance, and also has the effects of oxygen isolation and smoke suppression: the released water vapor can dilute the oxygen concentration, while inhibiting the smoke produced by the combustion of organic components such as cellulose fibers, improving the safety during fire. The preferred addition amount of magnesium hydroxide is 1-5 parts, which can work synergistically with other flame retardants, and also can improve the overall flame retardant grade of the slab, meeting the use requirements in places with strict requirements on fire performance, and the most preferred is 2-3 parts.
[0059] The fibers are also used in the present application to enhance the mechanical properties and prevent cracking and delamination, and the core role is to improve the tensile and bending resistance of the plate through the "bridging effect" to avoid cracking due to stress such as phase change expansion and temperature change during forming or use. The preferred fibers are glass fiber, nylon fiber and cellulose fiber. Among them, the glass fiber as a high-strength skeleton can enhance the overall mechanical strength of the plate, especially the impact resistance of the thermal insulation layer (mainly inorganic components); it has good affinity with inorganic thermal insulation materials such as glass microspheres and aerogels, and is not easy to delaminate due to interface separation, and the preferred amount is 0.5-3 parts. The nylon fiber is used for toughness compensation, which can compensate for the brittleness of the glass fiber and improve the bending resistance of the plate such as handling and installation during construction; it has good compatibility with the adhesive PVA, which can enhance the cohesion of the bonding system and reduce internal cracking caused by the expansion of the phase change material; the preferred amount is 0.5-2.5 parts. The cellulose fiber is used for forming property improvement, and the surface of the cellulose fiber has hydroxyl groups, which can form hydrogen bonds with the hydroxyl groups of PVA to enhance the plasticity of the blank, especially during S6 segmenting roll forming, to reduce damage caused by extrusion; the preferred amount of cellulose fiber is 0.5-2.5 parts. The fibers used in the present application are preferably used in combination with three kinds, and through the combination of "inorganic reinforcement + organic toughening + hydrogen bond bridging", the strength and toughness of the plate are balanced to ensure the stability of the forming and the reliability of the long-term use.
[0060] In the preparation method of the phase change microcapsule composite aerogel thermal insulation material provided by the present application, polyvinyl alcohol (PVA) solution is preferably prepared separately first to ensure that PVA is fully dissolved. Two types of PVA (different polymerization degrees: 1788 about 1700, 2488 about 2400) are mixed and dissolved to accurately adjust the bonding strength, film forming property and viscosity, and meet the subsequent bonding requirements. Dissolving polyvinyl alcohol separately can avoid premature contact with other ingredients (such as boric acid), because PVA is prone to cross-linking reaction with boric acid to form borate ester bonds. If mixed in advance, partial cross-linking of PVA may occur before it is fully dissolved, resulting in clumping and affecting the uniformity of the solution. If PVA is directly mixed with boric acid, silica sol and other ingredients, PVA may not be uniformly dispersed due to insufficient dissolution, and premature cross-linking with boric acid may cause a sudden increase in solution viscosity and clumping, making it impossible to uniformly mix with other materials subsequently, and finally resulting in local bonding failure of the plate.
[0061] Dissolving boric acid separately can ensure that it is fully dissolved (boric acid has low solubility and needs to be stirred thoroughly) to avoid uneven cross-linking caused by undissolved boric acid particles; silica sol (inorganic nanoparticles) has the best stability at weak alkaline pH (strong acidity or strong alkalinity tends to agglomerate), and adding it after adjusting the pH can prevent agglomeration and ensure uniform dispersion of the inorganic phase, thereby enhancing the heat resistance and mechanical strength of the plate); the hydrophobic agent is more stable under neutral conditions, avoiding emulsion breakage due to pH fluctuations to ensure its uniform distribution to improve the water resistance of the plate.
[0062] The present application finds through a large number of experiments that the reaction sequence needs to be controlled, because boric acid is used as a crosslinking agent for PVA, and needs to be kept in a free state before being mixed with PVA (S3), and is prepared separately to avoid its reaction with other components (such as fibers, thermal insulation materials) in advance, and to ensure efficient crosslinking with PVA subsequently; if the step-by-step processing is skipped, such as adding silica sol directly without adjusting pH, or adding a hydrophobic agent first and then adjusting pH, it will lead to: silica sol agglomeration, thereby losing the enhancement effect, hydrophobic agent demulsification, thereby leading to the failure of waterproofness, and undissolved boric acid, thereby leading to uneven crosslinking reaction, and finally poor dispersibility of solution B, and after being mixed with solution A, a uniform system cannot be formed. When solution A (PVA) is mixed with solution B (boric acid, etc.), crosslinking reaction occurs between the hydroxyl groups of PVA and the hydroxyl groups of boric acid (a three-dimensional network is gradually formed), at this time, mixing can ensure that the crosslinking reaction proceeds in a uniform system, and local overcrosslinking is avoided. Bubbles are easily generated during the mixing process, especially when PVA reacts with boric acid, and adding a defoaming agent separately can accurately eliminate bubbles, and avoid the residual bubbles from causing pores in the board, thereby affecting the mechanical strength and thermal insulation property. If A and B are mixed in advance (or no separate defoaming agent is added), it may lead to: crosslinking reaction proceeds too early, the viscosity of the solution rises sharply, and mixing is uneven (local over-thickening or over-thinning); bubbles are not eliminated, and the final board contains a large number of air holes, the mechanical strength is reduced, and the thermal insulation / energy storage performance is unstable. Therefore, polyvinyl alcohol needs to be dissolved first as solution A, boric acid is then dissolved in water, silica sol is then added, stirring is uniformly performed, the pH value is then adjusted, a hydrophobic agent is then added, stirring is uniformly performed, and then solution B is obtained; solution A is then mixed with solution B, and finally a defoaming agent is added to eliminate bubbles, and a bonding solution is obtained.
[0063] In the present application, the phase change energy storage layer contains a large number of phase change microcapsules, and the thermal insulation layer does not contain such components, and the material properties of the two are obviously different. Among them, the phase change energy storage layer mixture needs to be prepared separately, because the phase change energy storage layer needs to contain phase change materials (the core function is heat storage / heat release), and separate mixing can ensure that the phase change materials are only concentrated in the energy storage layer, and avoid being mixed into the thermal insulation layer, which would otherwise affect the low thermal conductivity of the thermal insulation layer. Ensure the synergistic effect of each component: fibers (enhance mechanical properties), flame retardants (fireproofing), and phase change materials, thermal insulation materials are uniformly dispersed in the bonding solution, and ensure that the energy storage layer has heat storage, mechanical strength and flame retardancy. If the phase change materials are mixed into the thermal insulation layer, such as being combined with S5, it will lead to: the thermal insulation layer has reduced thermal insulation effect due to the high thermal conductivity of the phase change materials or the change in heat conduction during the phase change process; the energy storage layer has reduced heat storage capacity due to insufficient phase change material content, and the functional layer is invalid.
[0064] In the present application, the thermal insulation layer mixture is prepared separately, and 1 can focus on the thermal insulation function: because the thermal insulation layer does not need phase change materials, and only through the synergistic effect of thermal insulation materials such as hydrophobic aerogel powder, glass microspheres, expanded perlite, carbon black, flame retardants and fibers, the low thermal conductivity and mechanical strength are ensured, and separate preparation can avoid the interference of other components (such as phase change materials) with the thermal insulation performance.
[0065] 2. Forming a performance gradient with the energy storage layer: the difference in composition between the thermal insulation layer and the energy storage layer (whether or not there is a phase change material, different thermal conductivity) is the basis for "gradient compounding", and the density, porosity and other parameters of the two layers can be precisely controlled when prepared separately, to achieve complementary functions. If combined with S4, the thermal insulation layer will have a higher thermal conductivity due to the mixing of phase change materials, losing its insulation function; at the same time, the composition of the two layers is confused, and the gradient structure cannot be formed, and the overall board loses the synergistic effect of "heat storage + thermal insulation".
[0066] In the preparation method of the present application, by using segmented roller process, segmented roller (multiple rollers gradually pressurized) can avoid mixing or interface peeling of two layers of materials caused by one-time high pressure, ensure the interface bonding of the phase change energy storage layer and the thermal insulation layer, and at the same time retain the microstructure of each layer such as the distribution of phase change materials in the energy storage layer and the porous structure of the thermal insulation layer, so that the gradient structure is stably combined. By adjusting the pressure of each segment of the roller, the thickness and density of the two layers can be precisely controlled to ensure the overall dimensional stability of the board and the uniformity of the performance, such as the consistent thermal insulation / heat storage performance of the edge and the center, and the controllable thickness and density. It can also allow the two types of mixtures to maintain uniform dispersion of components during compounding, effectively preventing local agglomeration or delamination, and ensuring the consistency of the performance of each layer of material. If one-time extrusion molding is used, it may cause: excessive mixing of the two layers of materials, losing the gradient function; insufficient interface bonding, delamination during use; local pressure too high to damage the structure of the phase change material or the thermal insulation material (such as phase change material leakage, thermal insulation material pores being compacted), resulting in a significant decrease in the performance of the board. Therefore, the segmented roller process is preferred, with a segmented extrusion pressure of 0.3-0.5 MPa and a roller rotation speed of 25-30 mm / s. The pressure of each segment is the same, and the roller rotation speed is also consistent.
[0067] The present application finally undergoes a curing process, preferably at a temperature of 60-80°C for 6-7h, which can promote the complete cross-linking reaction of PVA and boric acid, forming a stable three-dimensional network structure, firmly binding the components in the phase change energy storage layer and the thermal insulation layer such as phase change materials, thermal insulation materials, fibers, etc., and avoiding the migration of components such as phase change material leakage during subsequent processing or use. By curing, the initial mechanical strength of the board is improved, so that it is not prone to deformation such as warping and cracking during the drying process, providing a stable structural basis for subsequent drying.
[0068] Finally, drying can remove the excess water in the board, avoiding the influence of residual water on the thermal insulation performance of the material. The thermal conductivity of water is much higher than that of aerogel and other thermal insulation materials. Residual water will cause the thermal insulation effect to decrease. For phase change microcapsules, drying can ensure that they are in a stable state, avoiding the rupture of the microcapsule shell caused by a humid environment, and restoring the porous structure of aerogel and other thermal insulation materials. The thermal insulation of aerogel depends on its nano-porous structure. Water will fill the pores and destroy the thermal insulation capacity. The preferred drying temperature is 100-130℃, and the drying time is 12-13h. After drying, the density of the board decreases, making it easier to transport and install, and it can maintain a stable shape for a long time, avoiding mold growth or structural aging caused by moisture.
[0069] If not solidified and directly dried: the cross-linking reaction of PVA and boric acid is not completely performed, the network structure is loose, and the rapid loss of water during the drying process will cause uneven internal stress of the material, resulting in serious cracking and deformation; at the same time, the un-solidified bonding system cannot bind the phase change material and the thermal insulation material, which may cause the phase change material to seep out and the thermal insulation layer structure to collapse. If not dried or not completely dried after solidification: residual water will increase the thermal conductivity of the board, and the thermal insulation performance will decrease significantly; a humid environment will also cause the mold growth of fibers (such as cellulose fibers) and the failure of flame retardants (some flame retardants are prone to loss when exposed to water); long-term storage may cause the hydrolysis of the phase change microcapsule shell, resulting in the loss of heat storage function, and finally the overall performance of the board fails. Therefore, the above operation process cannot be reversed. The materials used in the present application can be purchased from the market. The phase change microcapsules can be purchased from Hefei Xinneng Phase Change Co., Ltd. with a phase change temperature of 28℃. The silica sol can be purchased from Guangdong Huihe Silicon Products Co., Ltd. The calcium stearate emulsion can be purchased from Guangzhou Zhenghao New Materials Technology Co., Ltd. In order to better explain the present application and facilitate understanding, the present application will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0070] Example 1
[0071] A preparation method of a phase change microcapsule composite aerogel thermal insulation material, specifically comprising the following steps:
[0072] 1. Preparation of phase change energy storage layer and thermal insulation layer mixture
[0073] ① Preparation of adhesive solution: 6 parts of polyvinyl alcohol 1788 and 6 parts of polyvinyl alcohol 2488 were mixed with 200 parts of deionized water, placed in a 90℃ magnetic stirrer at 2600r / min for stirring, and stirred for 2h until completely dissolved and then cooled to room temperature as solution A for standby;
[0074] Dissolve 1 part of boric acid in 50 parts of deionized water, then add 25 parts of silica sol, stir uniformly, add appropriate amount of acetic acid, adjust the pH to 7.5, then add 30 parts of calcium stearate emulsion, and stir at 2000r / min in a magnetic stirrer at room temperature for 3min, as solution B for standby;
[0075] Finally, solution A and solution B are mixed, and 1 part of tributyl phosphate is added to defoam. After the foam in the solution disappears under slight stirring, the adhesive solution is obtained.
[0076] ②Mixing of the powder and the solution
[0077] 30 parts of phase change microcapsules, 5 parts of silica aerogel powder, 25 parts of hollow glass microspheres, 15 parts of floating beads, 10 parts of expanded perlite, 2 parts of carbon black, 5 parts of talc, 5 parts of montmorillonite, 2 parts of magnesium hydroxide, 2 parts of glass fiber, 2 parts of nylon fiber, and 1 part of cellulose fiber are weighed, and the above materials are put into a blender for uniform dry mixing at 200 r / min for 2 min.
[0078] After the above powder and fiber are uniformly dry mixed, the adhesive solution obtained in step 1 is poured into the blender, and the blender is set to stir at 250 r / min for 5 min to form a plastic state mixture of the phase change energy storage layer.
[0079] ③The adhesive solution is prepared according to the same formula and process as in 1, and the powder formula in 2 is not added with phase change microcapsules. Specifically, 5 parts of silica aerogel powder, 25 parts of hollow glass microspheres, 15 parts of floating beads, 10 parts of expanded perlite, 2 parts of carbon black, 5 parts of talc, 5 parts of montmorillonite, 2 parts of magnesium hydroxide, 2 parts of glass fiber, 2 parts of nylon fiber, and 1 part of cellulose fiber are weighed, and the above materials are put into a blender for uniform dry mixing at 200 r / min for 2 min. After uniform mixing, the adhesive solution obtained in step 1 is poured into the blender, and the blender is set to stir at 250 r / min for 5 min to obtain a plastic state mixture of the thermal insulation layer.
[0080] 2. Forming of the board
[0081] The mixture obtained in step 1 is formed by a pair of roller forming process, which mainly applies pressure to the mixture through two counter-rotating rollers to realize forming. For the preparation of phase change microcapsule composite aerogel products, a segmented pair of roller process is used for compounding, and the pressure of segmented extrusion is 0.5 MPa, and the roller rotation speed is 25 mm / s. The plastic state mixture of the phase change energy storage layer and the plastic state mixture of the thermal insulation layer are uniformly and gradiently compounded and formed under the action of segmented extrusion, and the material composition along the thickness direction presents a continuous and smooth and uniform distribution. The thickness of the thermal insulation layer and the phase change energy storage layer is 10 mm, and the total thickness after gradient compounding is 20 mm.
[0082] 3. Drying
[0083] Put the shaped plate into the oven for the first stage of curing, the curing temperature is 60℃, the curing time is 6h, dry the cured plate, the drying temperature is 100℃, the drying time is 12h; after drying, the phase change microcapsule composite aerogel plate is obtained.
[0084] Example 2
[0085] 1. Preparation of phase change energy storage layer and thermal insulation layer mixture
[0086] ① Preparation of bonding solution
[0087] Take 8 parts of polyvinyl alcohol 1788 and 10 parts of polyvinyl alcohol 2488, mix with 300 parts of deionized water, place in a 90℃ magnetic stirrer 2600r / min for stirring, stir for 2h until completely dissolved, then cool and set aside as solution A;
[0088] Dissolve 2 parts of boric acid in 50 parts of deionized water, then add 25 parts of silica sol, stir evenly, then add appropriate amount of acetic acid, adjust pH to 7.5, then add 25 parts of calcium stearate emulsion, stir at room temperature in a magnetic stirrer at 2000r / min for 3min, then set aside as solution B;
[0089] Finally, mix solution A and solution B, add 2 parts of tributyl phosphate for defoaming, use a glass rod to stir slightly until the foam in the solution disappears, and obtain the bonding solution.
[0090] ② Mixing of powder and solution
[0091] Take 40 parts of phase change microcapsules, 15 parts of silica aerogel powder, 30 parts of hollow glass microspheres, 18 parts of floating beads, 15 parts of expanded perlite, 1 part of carbon black, 7 parts of talc, 8 parts of montmorillonite, 3 parts of magnesium hydroxide, 1 part of glass fiber, 1 part of nylon fiber, and 2 parts of cellulose fiber. Put the above materials into a blender and mix evenly at 250r / min for 3min;
[0092] After the above powder and fiber are dry-mixed evenly, pour the solution prepared in step ① into the blender, set the blender to 250r / min and stir for 4min to form a plastic state mixture of the phase change energy storage layer.
[0093] ③ The bonding liquid is prepared according to the same formula and process as in ① above; and the formula in ② above is used without the phase change microcapsules, specifically, 15 parts of silica aerogel powder, 30 parts of hollow glass microspheres, 18 parts of float beads, 15 parts of expanded perlite, 1 part of carbon black, 7 parts of talc, 8 parts of montmorillonite, 3 parts of magnesium hydroxide, 1 part of glass fiber, 1 part of nylon fiber, and 2 parts of cellulose fiber are weighed, and the above materials are put into a blender for uniform dry mixing, after 3 min of stirring at 250 r / min, the bonding liquid solution prepared in step ① above is poured into the blender, and the blender is set to stir at 250 r / min for 4 min to form a plastic state mixture of the thermal insulation layer.
[0094] 2. Forming of the board
[0095] The mixture obtained in step 1 is subjected to a roll forming process, which mainly applies pressure to the mixture through two counter-rotating rollers to achieve forming. For the preparation of the phase change microcapsule composite aerogel board product, a segmented roll process is used for compounding, and the pressure of the segmented extrusion is set to 0.4 MPa, and the roll rotation speed is set to 28 mm / s. The phase change energy storage layer plastic state mixture and the thermal insulation layer plastic state mixture are uniformly compounded and formed under the action of segmented extrusion.
[0096] 3. Drying
[0097] The formed board is placed in an oven for the first stage of curing, with a curing temperature of 80°C and a curing time of 7 h, and the cured board is dried at a drying temperature of 120°C for 13 h. After drying, a phase change microcapsule composite aerogel board is obtained.
[0098] The thickness of the thermal insulation layer and the phase change energy storage layer is 10 mm, and the total thickness after gradient compounding is 20 mm. The structure of the obtained phase change microcapsule composite aerogel board is shown in FIG. 2.
[0099] Comparative Example 1
[0100] Comparative Example 1 is the preparation of a traditional uniform phase change board, which uses the same preparation method, process and drying process as in Example 1, except that the thermal insulation layer is replaced by a phase change energy storage layer with the same thickness and formula. Two 10 mm phase change energy storage boards with the same formula are prepared, with a total thickness of 20 mm, and the structure is shown in FIG. 1. Figure 2 Since the board in this comparative example is not gradient compounded, it is referred to as uniform phase change board 1.
[0101] Comparative Example 2
[0102] Preparation of the homogeneous insulation board of the conventional structure in Comparative Example 2, the preparation method, process and drying process are the same as those in Example 1, the difference is that the phase change energy storage layer is replaced by an equal thickness and equal formula heat insulation layer, two layers of 10 mm of the same formula heat insulation board are prepared, and the total thickness is 20 mm, and the structure diagram is shown in Figure 3 . Since the board in the comparative example is not gradiently compounded, it is called homogeneous insulation board 2.
[0103] Comparative Example 3
[0104] In order to explore the synergistic effect of phase change microcapsules and aerogels in the board, Comparative Example 3 is prepared by increasing the amount of phase change microcapsules. The preparation method, process and drying process of Comparative Example 3 and Example 2 are the same, the difference is that the formula of the phase change energy storage layer is changed, only the amount of phase change material is increased, the added phase change microcapsules are 60 parts, and the structure diagram of the obtained product is shown in Figure 4 . It is found that when the ratio of phase change material to heat preservation material in the phase change layer is changed, the synergistic effect of the two is also changed.
[0105] The products of each example and comparative example are tested by differential scanning calorimetry (DSC) for enthalpy value test. The measured enthalpy value of the phase change microcapsule composite aerogel board prepared in Example 1 is 173.8 J / g, the measured enthalpy value of the phase change microcapsule composite aerogel board prepared in Example 2 is 181.5 J / g, the measured enthalpy value of the homogeneous phase change board prepared in Comparative Example 1 is 357.7 J / g, the enthalpy value of the homogeneous insulation board prepared in Comparative Example 2 is 0 J / g; the measured enthalpy value of the phase change microcapsule composite aerogel board prepared in Comparative Example 3 is 209.6 J / g.
[0106] Since the amounts of phase change microcapsules in Example 1, Example 2 and Comparative Example 3 are 30 parts, 40 parts and 60 parts respectively, the enthalpy values of Example 1, Example 2 and Comparative Example 3 show a trend from small to large, which are 173.8 J / g, 181.5 J / g and 209.6 J / g respectively. Comparative Example 1 and Comparative Example 2 are homogeneous phase change board and homogeneous insulation board respectively. The tested enthalpy value of Comparative Example 1 is 357.7 J / g; no phase change microcapsules are added in Comparative Example 2, so the tested enthalpy value is 0 J / g. It shows that the heat absorption capacity of Example 1 and 2 is lower than that of Comparative Example 3 and Comparative Example 1.
[0107] The thermal conductivity is tested according to the standard GB / T 10295-2008 "Determination of thermal resistance and related properties of thermal insulation materials by heat flow meter method". The measured results are as follows:
[0108] The thermal conductivities of Example 1 and Example 2 are 0.0492 W / (m·K) and 0.0498 W / (m·K) respectively, and the data difference is very small, indicating that the synergistic ratio of the phase change material and the thermal insulation material of the application has good stability - even if the formula parameters are slightly adjusted, the thermal conductivity level can still be maintained at a low and stable level, verifying the reliability of the formula design.
[0109] Comparative Example 1 is a "uniform phase change plate", and the thermal conductivity is as high as 0.0698 W / (m·K), which is much higher than each of the examples. This is because the excess phase change microcapsules have relatively strong thermal conductivity, and the continuous heat insulation structure of the thermal insulation material is destroyed, resulting in accelerated heat transfer rate, which confirms the technical pain point that "simply increasing the amount of phase change material will sacrifice the thermal insulation performance".
[0110] Comparative Example 2 is a "uniform thermal insulation plate", and the thermal conductivity is 0.0303 W / (m·K), which is low, but it lacks the heat storage regulation of the phase change material, and can only delay temperature change through physical heat insulation (no "phase change temperature control plateau" in the examples). This comparison highlights the necessity of the "phase change heat storage + thermal insulation heat insulation" synergistic design of the application - it not only solves the defect of "no temperature control ability" of single thermal insulation material, but also avoids the problem of "high thermal conductivity" of single phase change material.
[0111] Comparative Example 3 has a thermal conductivity of 0.0568 W / (m·K), which is higher than each of the examples. The core reason is that the amount of phase change material exceeds the synergistic ratio of the application. Excessive phase change material leads to an increase in the thermal conductivity of the system, directly weakening the thermal insulation performance, further demonstrating the innovation of the application "precise control of the amount of phase change and thermal insulation materials" - by balancing the proportion of the two, the synergistic advantage of "low thermal conductivity + long-term temperature control" is achieved. At the same time, excessive phase change material will also sacrifice the strength and flame retardancy of the thermal insulation material.
[0112] Heating table test:
[0113] To verify the performance of the aerogel plate and the gradient composite phase change microcapsule aerogel plate prepared by the formula and preparation of the application, the products of the examples and comparative examples are placed on a heating table with a hot surface temperature of 80℃, and the obtained temperature-time curve is as follows Figure 5As shown, the specific analysis is as follows: the temperature curve of Example 1 presents an obvious platform period, and the corresponding time length is 1000s-1100s, which embodies the characteristics of the aerogel plate delaying temperature rise by using phase change heat storage. Comparative Example 1 and Comparative Example 2 are compared with Example 1 respectively. The platform period of Comparative Example 1 is only about 500s, because it does not set a heat preservation layer, and the phase change microcapsule itself has relatively good thermal conductivity, the heat transfer rate is fast, which leads to a significant shortening of the effective platform period of heat storage and temperature control, and cannot long-term delay temperature rise; Comparative Example 2 is a uniform heat preservation plate, and the temperature curve has no platform period, and the temperature directly continues to rise after heat input. Because the uniform heat preservation plate only relies on a single heat insulation material, it lacks the "temperature buffer" mechanism of phase change heat storage, and cannot realize the temperature control platform effect similar to the phase change microcapsule-containing system. Comparative Example 3 is compared with Example 2, and the platform period of Example 2 is about 1100s, which exhibits good heat storage and temperature control persistence. The platform period of Comparative Example 3 is between 700s-800s, which is significantly shorter than Example 2. This difference shows that the more phase change microcapsules, the better the heat preservation and insulation effect - in theory, increasing the amount of phase change microcapsules can increase the enthalpy value (heat storage potential) of the material, but at the same time, it increases the thermal conductivity of the system, which actually weakens the overall heat preservation and insulation performance of the aerogel plate.
[0114] As can be seen, by accurately regulating the synergistic ratio of phase change materials (phase change microcapsules) and heat preservation materials (such as aerogels, etc.), the present application breaks through the traditional thinking limitations of "single increase of phase change microcapsule content", realizes efficient synergy of phase change heat storage and heat preservation and insulation, verifies the innovation and rationality of the formula design, and ensures that the aerogel plate has better temperature control time and heat preservation performance.
[0115] The above is only a preferred embodiment of the present application, and is not intended to limit the present application in other forms. Any person skilled in the art can modify or modify the above disclosed technical content as equivalent embodiments. However, any simple modification, equivalent change and modification of the above embodiments according to the technical essence of the present application still belongs to the protection scope of the present application.
Claims
1. A phase change microcapsule composite aerogel thermal insulation material, characterized in that, It comprises a phase change energy storage layer and a thermal insulation layer, The phase change energy storage layer is prepared from energy storage powder and adhesive, the energy storage powder comprises thermal insulation material, phase change material, flame retardant and fiber; the phase change material is phase change microcapsule; The thermal insulation layer is prepared from thermal insulation powder and adhesive, the thermal insulation powder comprises thermal insulation material, flame retardant and fiber; In the energy storage powder and the thermal insulation powder, the thermal insulation material is a combination of glass microspheres, hydrophobic aerogel powder, floating beads, expanded perlite and carbon black; the flame retardant is a combination of montmorillonite, talc powder and magnesium hydroxide; the fiber is a combination of glass fiber, nylon fiber and cellulose fiber; the adhesive comprises polyvinyl alcohol, boric acid and silica sol; In the preparation of the phase change energy storage layer and the thermal insulation layer, the adhesive is configured into adhesive liquid with water, defoaming agent and hydrophobic agent.
2. The phase change microcapsule composite aerogel thermal insulation material according to claim 1, characterized in that, The thermal insulation material is 56-90 parts by mass, the phase change material is 30-40 parts by mass, the flame retardant is 12-23 parts by mass, and the fiber is 3-6 parts by mass; the adhesive is 33-52 parts by mass, the defoaming agent is 1-2 parts by mass, the water is 250-350 parts by mass, and the hydrophobic agent is 20-30 parts by mass; the defoaming agent is tributyl phosphate, and the hydrophobic agent is calcium stearate emulsion.
3. The phase change microcapsule composite aerogel thermal insulation material according to claim 2, characterized in that, The thermal insulation material comprises 20-35 parts by mass of glass microspheres, 3-20 parts by mass of hydrophobic aerogel powder, 12-20 parts by mass of floating beads, 8-18 parts by mass of expanded perlite and 0.5-5 parts by mass of carbon black; the flame retardant comprises 3-10 parts by mass of montmorillonite, 2-9 parts by mass of talc powder and 1-5 parts by mass of magnesium hydroxide; and the fiber comprises 0.5-3 parts by mass of glass fiber, 0.5-2.5 parts by mass of nylon fiber and 0.5-2.5 parts by mass of cellulose fiber.
4. The phase change microcapsule composite aerogel thermal insulation material according to claim 2, characterized in that, The thermal insulation material comprises 25-30 parts by mass of glass microspheres, 5-15 parts by mass of hydrophobic aerogel powder, 15-18 parts by mass of floating beads, 10-15 parts by mass of expanded perlite and 1-2 parts by mass of carbon black; the flame retardant comprises 5-8 parts by mass of montmorillonite, 5-7 parts by mass of talc powder and 2-3 parts by mass of magnesium hydroxide; and the fiber comprises 1-2 parts by mass of glass fiber, 1-2 parts by mass of nylon fiber and 1-2 parts by mass of cellulose fiber.
5. The method for preparing the phase change microcapsule composite aerogel insulation material according to any one of claims 1-4, characterized in that, It comprises the following steps: S1, polyvinyl alcohol is mixed with water and stirred to dissolve, as solution A; S2, boric acid is dissolved in water, then silica sol is added, stirred uniformly, pH value is adjusted to weak alkaline, hydrophobic agent is added and stirred uniformly, as solution B; S3, solution A is mixed with solution B, defoaming agent is added and defoamed, to obtain adhesive liquid; S4, thermal insulation material, phase change material, flame retardant and fiber are uniformly mixed, then mixed with adhesive liquid, to obtain phase change energy storage layer plastic state mixture; S5, thermal insulation material, flame retardant and fiber are uniformly mixed, then mixed with adhesive liquid, to obtain thermal insulation layer plastic state mixture; S6, using segmented roller process, phase change energy storage layer plastic state mixture and thermal insulation layer plastic state mixture are uniformly and gradiently compounded and formed under segmented extrusion, to obtain plate blank; S7, the plate blank is first solidified, then dried, to obtain phase change microcapsule composite aerogel plate.
6. The production method according to claim 5, wherein In step S1, the stirring dissolving is carried out at 80-100℃, the stirring rate is 2000-3000r / min, and the stirring time is 1.5-3h.
7. The production method according to claim 5, wherein In step S2, the pH is adjusted to 7.5 by using an acidic reagent; the stirring rate for stirring and mixing is 1500-2500r / min, and the stirring time is 2-4min.
8. The production method according to claim 5, wherein In steps S4 and S5, the stirring rate for stirring and mixing with the bonding liquid is 200-300r / min, and the stirring time is 2-5min.
9. The production method according to claim 5, wherein In step S6, the pressure for the sectional extrusion in the sectional roll process is 0.3-0.5MPa, and the roll rotating speed is 25-30mm / s.
10. The production method according to claim 5, wherein In step S7, the curing temperature is 60-80℃, the curing time is 6-7h; the drying temperature is 100-130℃, and the drying time is 12-13h.
Citation Information
Cited By
Inorganic silicon crystal fireproof thermal insulation material for fireproof air duct and preparation method of inorganic silicon crystal fireproof thermal insulation material
CN121318360A